Reversible Thinking of Fifth Graders: Focus on Linier Equations - Syarifatul Maf'ulah (Jurnal Ilmiah Sekolah Dasar, 2022)
Reversible thinking is the mental ability to return the way of thinking to the original point. This study explores the reversible thinking of fifth graders on linear equations. This descriptive-exploratory research was conducted on 96 fifth-grade elementary school students. Data collection is done by providing reversible thinking and interviews. The technique used for data analysis is qualitative and quantitative description analysis. The assignment contains a linear equation (called the initial equation). Students are asked to make an equation equivalent to the initial equation. All equations that students successfully created were then analyzed and classified based on the strategies used. Next, one student with the most diverse approach was selected to be explored more deeply in reversible thinking. The results of the study, there are ten categories of students' reversible thinking strategies, among others, first, moving the elements of the initial equation builder. Second, determine the unknown factors. Third, operate both sides of the initial equation with the same number. Fourth, operate both as equations of equivalent expressions. Fifth, change the known building elements in the created equation. Sixth refers to the value of the unknown component then converts that value into a presentation. Seventh, transforming the building elements that are known in the initial equation. Eighth refers to the value of the initial equation variable. Ninth, using the definition of subtraction. Tenth, using the commutative property of the operation of the number.